Computational thinking: associated skills and teaching resources (Innovaciones Educativas, 2021)
Today's society requires that future citizens be prepared in digital skills. Precisely, computational thinking could be one of the ways to promote this new literacy. In this sense, the objective of this article is to analyze empirical studies regarding associated skills and didactic resources for the development of computational thinking. An exhaustive search was carried out in two databases: EBSCO and SCOPUS between the years 2017 and the first semester of 2021, obtaining 15 articles for the review. According to the analysis of the collected evidence, it was identified that the most recurrent skills are: computational concepts and practices and pedagogical perspectives. In addition to the abstraction, pattern recognition, decomposition and algorithm associated with problem solving. Robotics and the programming language are the most frequently used resources in pedagogical experiences. Being regular basic education, with 60%, the most studied level. Therefore, computational thinking is feasible to be brought into the classroom from an early age, but it is necessary for teachers to know the different strategies and languages ​​in order for students to acquire the skills of the 21st century.
Keywords: Education; skills; digital literacy; robotics; programming language